OP0197 Rheumatic and musculoskeletal adverse events associated with immune checkpoint inhibitors: data mining of the us food and drug administration adverse event reporting system. (12th June 2018) - Pundole, X.; Sarangdhar, M.; Suarez-Almazor, M.E.
Abstract : Background: Immune-modulating monoclonal antibodies directed against immune checkpoints ((cytotoxic T lymphocyte-associated antigen 4 (CTLA-4), programmed cell death-1 receptor (PD-1) and its ligand PD-L1)), have demonstrated tremendous promise in the treatment of diverse solid tumour types, including melanoma, non-small cell lung cancer, among others and have improved survival rates of these cancer patients. However, these advances have created a new set of challenges in identifying and managing toxicities. Objectives: To identify emerging trends of rheumatic and musculoskeletal adverse events by immune checkpoint inhibitor (ICI) treatment in the US Food and Drug Administration (FDA) Adverse Events Reporting System (FAERS). Methods: We used AERSMine, an open-access web based application to mine the FAERS database from the first quarter (Q1) of 2011 to the third quarter (Q3) of 2017, approximately 7.1 million patients. Measures of disproportionality were calculated using well-established pharmacovigilance metrics, Relative Risks (RR) and safety signals (information component, (IC)), in a subset of patients with a cancer diagnosis. Terminology used for categorization of adverse events was as included in the FAERS. Fisher's exact test was used to determine significant adverse event differences by ICI treatment and age. Results: We identified 30 939 unique patients with cancer and reports of immune checkpoint inhibitor associated toxicities. More than half of these reports were in relation with anti PD-1 inhibitors. Statistically significant adverse events associated with ICI therapy identified as toxicity signals with different agents included: 1 NIVOLUMAB: myositis (n=102; RR, 1.35; p<0.01; IC, 0.43), rheumatoid arthritis (n=67; RR, 1.52; IC, 0.61), psoriatic arthropathy (n=20; RR, 1.93, IC, 0.95), musculoskeletal pain (n=76; RR, 1.37; IC, 0.45) and myasthenia gravis (n=66; RR, 1.42; IC, 0.50); 2 PEMBROLIZUMAB: arthralgia (n=151; RR, 1.43; IC, 0.52) and pain in an extremity (n=58; RR, 1.35; IC, 0.43); 3 DURVALUMAB: polymyositis (n=2; RR, 4.41; IC, 2.15), rhabdomyolysis (n=4; RR, 2.68; IC, 1.42), and autoimmune arthritis (n=2; RR, 8.83; IC, 3.14); 4 IPILIMUMAB: muscular weakness (n=157; RR, 1.70; IC, 0.76) and back pain (n=105; RR, 1.27; IC, 0.34). In general, rates of rheumatic and musculoskeletal adverse events were higher in men and in the elderly population (>65 years). Conclusions: A wide spectrum of rheumatic and musculoskeletal toxicity signals were detected with ICI's. Clinicians need to be vigilant about these rare but debilitating complications. Future studies to explore mechanisms and optimal management strategies of these toxicities are warranted. Reference: [1] Sarangdhar M, Tabar S, Schmidt C, et al. Data mining differential clinical outcomes associated with drug regimens using adverse event reporting data. Nat Biotechnol2016;34:697–700. Disclosure of Interest: None declared